Assessing the long-term efficacy of internal loading management to control eutrophication in Lake Rauwbraken. Issue 1 (2nd January 2022) - van Oosterhout, Frank; Yasseri, Said; Noyma, Natalia; Huszar, Vera; Manzi Marinho, Marcelo; Mucci, Maíra; Waajen, Guido; Lürling, Miquel
ABSTRACT: Lake Rauwbraken was impacted by eutrophication caused by diffuse external phosphorus (P) loads (total 1.21 mg m −2 d −1, estimated in 2008). Over 40 years, this load built up a legacy pool in the sediments, resulting in 6.82 mg m −2 d −1 PO4 -P internal load (estimated in 2008), causing cyanobacterial blooms and swimming bans. To address the internal load in this lake, a low dose treatment of flocculant (polyaluminium chloride) combined with a solid phase phosphate fixative (lanthanum-modified bentonite) was applied in 2008. We examined the chemical and ecological responses to this treatment to demonstrate the efficacy of controlling internal loading without reducing external loading . Based on 2 years pre- and 10 years post-treatment monitoring, the mean Secchi disk depth (3.5–4.0 m) and the hypolimnetic oxygen concentration (0.86–4.55 mg L −1 ) increased while decreases occurred in turbidity (5.4 to 2.2 NTU), chlorophyll a (16.5 to 5.5 µg L −1 ), contribution of cyanobacteria (64% to 17% of chlorophyll a ), total phosphorus (134 to 14 µg L −1 ), and total nitrogen (0.96 to 0.50 mg L −1 ). The treatment reduced the PO4 -P release from sediment under anoxic conditions from 15.1 to 1.7 mg m −2 d −1 post-treatment in 2008, 2.3 mg m −2 d −1 in 2011, and 4.7 mg m −2 d −1 in 2013. Post-treatment, submerged macrophytes reached high coverage in 2008 and 2009. Longer term, post-treatment macrophyte cover was reduced. The lake is returning to a eutrophic state as a result of ongoing external P loads 10 years following the control of internal loading.